The Performance Analysis of Trans Metro Pekanbaru During the COVID-19 Pandemic - Muttaqin, Muchammad Zaenal; Ramanda, Irfan; Zaini, Abdul Kudus; Kumalasari, Cyintia (Universitas Negeri Semarang, 2024)
During the COVID-19 pandemic, the Trans Metro Pekanbaru bus manager limited the number of passengers, operating hours, and rit. This policy follows the implementation of the transition period towards a new normal in Pekanbaru City. This government policy’s enactment has influenced the performance of Trans Metro Pekanbaru public transportation during the COVID-19 pandemic. This study analyzes the performance of Trans Metro Pekanbaru public transportation during the COVID-19 pandemic based on passenger operations and perceptions. The research methods used in this study are quantitative and qualitative. The data analysis used is an analysis of operational performance data during the COVID-19 period and an analysis of passenger perceptions of service performance during the COVID-19 period. The results of this study show that the operational performance of Trans Metro Pekanbaru public transportation during the COVID-19 pandemic based on load factor, headway, and frequency indicators is considered insufficient. The average load factor value on all routes is below 70%, with the highest and lowest average values being 42% on the Ramayan – Pandau route and 2% on the Unilak – route Palas Kingdom. The average headway value on all routes is more than 10 minutes, with the highest average being 63 minutes on the BRPS – UIN and Ramayana – Unilak routes. The average frequency value on all routes only reaches 1-3 vehicles/hour, with the highest average being 5 vehicles/hour on the Ramayana route - Pandau. Based on passenger perception, it shows that passenger perception of the quality of Trans Metro Pekanbaru public transportation services during the COVID-19 pandemic is considered good. This can be seen from the average score of respondents’ assessment of 74.86%.